Completion of radical hysterectomy does not improve survival of patients with cervical cancer and intraoperatively detected lymph node involvement: ABRAX international retrospective cohort study. (January 2021) - Cibula, D.; Dostalek, L.; Hillemanns, P.; Scambia, G.; Jarkovsky, J.; Persson, J.; Raspagliesi, F.; Novak, Z.; Jaeger, A.; Capilna, M.E.; Weinberger, V.; Klat, J.; et al.
Abstract: Background: The management of cervical cancer patients with intraoperative detection of lymph node involvement remains controversial. Since all these patients are referred for (chemo)radiation after the surgery, the key decision is whether radical hysterectomy should be completed as originally planned, taking into account an additional morbidity associated with extensive surgical dissection prior to adjuvant treatment. The ABRAX study investigated whether completing a radical uterine procedure is associated with an improved oncological outcome of such patients. Patients and methods: We performed retrospective analyses of 515 cervical cancer patients (51 institutions, 19 countries) who were referred for primary curative surgery between 2005 and 2015 (stage IA–IIB, common tumour types) in whom lymph node involvement was detected intraoperatively. Patients were stratified according to whether the planned uterine surgery was completed (COMPL group, N = 361) or abandoned (ABAND group, N = 154) to compare progression-free survival. Definitive chemoradiation was given to 92.9% patients in the ABAND group and adjuvant (chemo)radiation or chemotherapy to 91.4% of patients in the COMPL group. Results: The risks of recurrence (hazard ratio [HR] 1.154, 95% confidence intervals [CI] 0.799–1.666, P = 0.45), pelvic recurrence (HR 0.836, 95% CI 0.458–1.523, P = 0.56), or death (HR 1.064, 95% CI 0.690–1.641, P = 0.78) were not significantly different between the two groups. No subgroup showed a survival benefit from completing radical hysterectomy. Disease-free survival reached 74% (381/515), with a median follow-up of 58 months. Prognostic factors were balanced between the two groups. FIGO stage and number of pelvic lymph nodes involved were significant prognostic factors in the whole study cohort. Conclusion: We showed that the completion of radical hysterectomy does not improve survival in patients with intraoperatively detected lymph node involvement, regardless of tumour size or histological type. If lymph node involvement is confirmed intraoperatively, abandoning uterine radical procedure should be considered, and the patient should be referred for definitive chemoradiation. Clinical trials identifier: NCT04037124 . Highlights: Radical hysterectomy does not improve outcome of N1 cervical cancer patients. Surgery completion brings no survival benefit irrespective of tumour size or type. If N1 is diagnosed intraoperatively, further radical procedure should be abandoned.